Perovskite solar cell containing silane-functionalized mxene
Patent Information
- Application Number
- CN202310543447.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-05-15
AI Technical Summary
[0029]1.本发明提供的钙钛矿太阳电池所采用的含极性基团的硅烷功能化MXene,可以有效降低MXene的功函数,并且,极性基团(如胺基)可以钝化缺陷和改善钙钛矿的结晶,从而提高电荷传输与抽取以及减少电荷复合,最终有效提高钙钛矿太阳电池性能。
Smart Images

Figure CN116744697B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite optoelectronic materials and devices technology, specifically relating to a perovskite solar cell containing silane-functionalized MXene. Background Technology
[0002] Solar cells are an efficient method for converting solar energy into electrical energy. Perovskite solar cells (PSCs) have attracted much attention due to their high efficiency, simple fabrication, and low cost. In recent years, their photoelectric conversion efficiency has rapidly increased to 25.5%, making them one of the fastest-growing types of thin-film solar cells. Although their photoelectric conversion efficiency exceeds 25.5%, their expensive metal electrodes and unstable hole transport layer limit their industrialization. Carbon electrodes possess stability and can replace the hole transport layer; using carbon electrodes is a promising low-cost method to replace metal electrodes. Therefore, carbon-based perovskite solar cells have received widespread attention and research.
[0003] In recent years, the development of two-dimensional MXene materials has attracted widespread attention. The introduction of different terminal chemical groups can regulate the surface potential, hydrophilicity, and work function of MXenes, and their introduction into PSCs can improve photovoltaic performance (Chen K, Cai P, Peng H, et al., J. Cent. South Univ. (2021) 28: 3935-3958). Surface groups have different effects on the Fermi level of MXenes; -O groups increase the work function of the MXene surface, -OH groups decrease the work function, and -F groups show different trends depending on the material. Furthermore, modifying MXenes with different small organic molecules can also effectively regulate their photoelectric properties. Regarding silane-modified MXenes, Jian-Bo Du et al. studied the modification of Ti3C2T with vinyltris(2-methoxyethoxy)silane (SCA). x MXene(SCA-Ti3C2T x The effect of SCA-Ti3C2T as a hole transport layer on the performance of perovskite solar cells is shown in the results. x This can enhance hole extraction and improve photovoltaic performance (Du JB, Yang L, Jin X, et al. Journal of Alloys and Compounds, 2022, 900: 163372.). Li Yin et al. modified Ti3C2T with dodecyltrimethoxysilane. xMXene (MH) was modified with SnO2 as an electron transport layer (SnO2-MH). The PCE of devices based on the SnO2-MH electron transport layer significantly increased from 20.98% to 23.66%, while also exhibiting better moisture resistance and operational stability (Yin L, Liu C, Ding C, et al. (2022). Cell Reports Physical Science, 3(6), 100905.). The silane-modified MXenes reported in the above literature use alkylsiloxanes, which do not contain polar groups and primarily serve to increase the work function and hydrophobicity of MXene. However, this invention uses silanes containing different polar groups to modify MXene, preparing silane-functionalized MXenes, and then incorporates them into tin oxide as an electron transport layer for use in perovskite solar cells. In this invention, MXene is modified with silane containing polar groups, which can effectively reduce the work function of MXene. Furthermore, polar groups (such as amine groups) can passivate defects and improve the crystallization of perovskite, thereby improving charge transport and extraction and reducing charge recombination, ultimately effectively improving the performance of perovskite solar cells. Summary of the Invention
[0004] To overcome the shortcomings and deficiencies of existing technologies, the present invention aims to provide a perovskite solar cell containing silane-functionalized MXene. The perovskite solar cell of the present invention, from bottom to top, comprises a transparent conductive glass, an electron transport layer, a perovskite active layer, and a carbon electrode. The electron transport layer is prepared by doping tin oxide with silane-functionalized MXene containing polar groups, wherein different polar groups can be introduced into the side chains of the silane. The use of silane-functionalized MXene containing polar groups in this invention can effectively reduce the work function of MXene. Furthermore, the polar groups (such as amine groups) can passivate defects and improve the crystallinity of the perovskite, thereby improving charge transport and extraction and reducing charge recombination, ultimately effectively improving the performance of the perovskite solar cell. The high-efficiency solar cell synthesis process provided by this invention is simple and easy to implement, requires low equipment requirements, and is easy to operate, showing good application prospects.
[0005] The term "MAX phase" in this invention refers to a non-metallic material composed of three elements, consisting of natural layered carbonitride compounds. It possesses the electrical and thermal conductivity of metals. The general chemical formula for MAX is M0. p+1 AX p (p = 1, 2, or 3), where M represents a transition metal element, A represents an element in group IIIA or IVA of the periodic table, and X represents carbon or nitrogen.
[0006] The objective of this invention is achieved through the following technical solution:
[0007] A perovskite solar cell containing silane-functionalized MXene includes an electron transport layer made of silane-functionalized MXene doped with tin oxide.
[0008] Furthermore, the silane has the general formula RSiY. m ,in,
[0009] R is selected from an alkyl chain or alkoxy chain containing a polar group, wherein the polar group is selected from one or more combinations of halogen, amino, mercapto, epoxy, cyano, and quaternary ammonium groups.
[0010] Y is selected from a hydrolyzable group, wherein the hydrolyzable group is selected from one or more combinations of halogen, methoxy, ethoxy or other alkoxy groups;
[0011] m is the number of the hydrolyzable groups, and m = 1-3.
[0012] Furthermore, the general formula of the MXene is M n+1 X n T x ,in,
[0013] M is selected from transition metal elements; the transition metal elements are selected from one or more combinations of Ti, Sc, Y, Zr, Hf, V, Nb, Ta, Cr, Mo, and W;
[0014] X is C or N;
[0015] n = 1 - 4;
[0016] T is selected from terminal functional groups; the terminal functional groups are selected from one or more combinations of -OH, =O, =S, =Se, =Te, -Br, -Cl or -F;
[0017] x is the number of terminal functional groups, and 0 <x≤2。
[0018] Furthermore, the perovskite solar cell containing silane-functionalized MXene has a structure that, from bottom to top, includes a transparent conductive glass, an electron transport layer, a perovskite layer, and a carbon electrode.
[0019] Furthermore, the method for preparing the electron transport layer includes the following steps:
[0020] S1. Preparation of silane-functionalized MXene:
[0021] The precursor MAX phase powder was placed in a lithium fluoride solution mixed with hydrochloric acid, stirred and reacted, and after centrifugation, the resulting product was added to ethanol, sonicated in an ice bath and centrifuged to obtain a layered MXene material; the layered MXene material was dispersed in a silane solution and stirred, washed, and the product was dispersed in a solvent and then sonicated in an inert atmosphere and ice bath to obtain a silane-functionalized MXene nanocolloid suspension.
[0022] S2, Fabrication of the electron transport layer:
[0023] The silane-functionalized MXene nanocolloid suspension was added to a tin oxide dispersion and mixed to obtain a precursor. The precursor was then spin-coated onto a substrate and annealed to obtain an electron transport layer.
[0024] Furthermore, the mass of the silane-functionalized MXene nanocolloid is 0.1%-30% of the mass of the tin oxide.
[0025] Furthermore, the annealing temperature is 100-180℃, and the annealing time is 20-40 minutes.
[0026] Furthermore, the spin coating speed is 3000-5000 rpm / s, and the spin coating acceleration is 1000-2000 rpm / s.
[0027] Further, the solvent is selected from one or more of deionized water, acetonitrile, N,N-dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, methanol, ethanol, isopropanol, n-butanol, tetrahydrofuran, chloroform, diethyl ether, isopropyl ether, n-butyl ether, trichloroethylene, diphenyl ether, dichloromethane, dichloroethane, toluene, xylene, chlorobenzene, dichlorobenzene, trichlorobenzene, cyclohexane, and hexane.
[0028] The present invention has the following beneficial effects:
[0029] 1. The perovskite solar cell provided by this invention uses silane functionalized MXene with polar groups, which can effectively reduce the work function of MXene. Furthermore, the polar groups (such as amine groups) can passivate defects and improve the crystallization of perovskite, thereby improving charge transport and extraction and reducing charge recombination, ultimately effectively improving the performance of perovskite solar cells.
[0030] 2. The perovskite solar cell provided by this invention utilizes Ti3C2T functionalized with silane containing polar groups. x MXene exhibits excellent stability, and under the same device fabrication conditions, silane-functionalized Ti3C2T containing polar groups... x MXene is superior to unfunctionalized Ti3C2T x MXene offers higher photoelectric conversion efficiency.
[0031] 3. The method for preparing high-efficiency and stable perovskite solar cells provided by this invention has a simple and easy synthesis process, low equipment requirements, and good prospects for industrial application. Attached Figure Description
[0032] Figure 1 The JV curves of the perovskite solar cells prepared in Examples 1-3 and Comparative Examples 1-2 are shown. Examples 1-3 are (3-aminopropyl)trimethoxysilane (APS), N-[3-(trimethoxysilyl)propyl]ethylenediamine (DAMO), and 3:3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane (APTES) functionalized Ti3C2T, respectively. x Perovskite solar cells fabricated using MXene-doped tin oxide as the electron transport layer; Comparative Examples 1-2 are pure tin oxide and pure Ti3C2T, respectively. x Perovskite solar cells fabricated using MXene-doped tin oxide as the electron transport layer.
[0033] Figure 2 The APS-Ti3C2T in Embodiment 1 of the present invention is shown. x MXene and Ti3C2T without silane functionalization in Comparative Example 2 x Infrared spectrum of MXene.
[0034] Figure 3 The APS-Ti3C2T in Embodiment 1 of the present invention is shown. x MXene and Ti3C2T without silane functionalization in Comparative Example 2 x X-ray photoelectron spectrum of MXene.
[0035] Figure 4 The silane-functionalized Ti3C2T described in Examples 1-3 is shown. x The structure of MXene perovskite solar cells. Detailed Implementation
[0036] To more clearly illustrate the technical solution of the present invention, the following preparation examples and embodiments are provided. Unless otherwise stated, the raw materials, reactions, and post-processing methods appearing in the preparation examples and embodiments are all commercially available raw materials and technical methods well known to those skilled in the art.
[0037] The perovskite layer used in the embodiments and comparative examples of the present invention is made of CH3NH3PbI3.
[0038] Example 1: A product containing APS-Ti3C2T x Fabrication of MXene perovskite solar cells
[0039] A type containing APS-Ti3C2T x MXene's perovskite solar cell has the following device structure: ITO (100nm) / Electron Transport Layer (ETL) (20nm) / Perovskite Layer (PVSK) (280nm) / Carbon Electrode (30μm).
[0040] The above contains APS-Ti3C2T x The fabrication method of MXene perovskite solar cells is as follows:
[0041] The preparation methods for ITO, perovskite layer, and carbon electrode are all processes and parameters well known to those skilled in the art.
[0042] Fabrication of the electron transport layer:
[0043] S1. Add 0.5 g LiF to 10 ml HCl (9 M) and stir for 5 min. Then, slowly add 0.5 g Ti3AlC2 over 5 min to avoid vigorous reaction. Stir the mixture continuously at 35 °C for 24 h. Centrifuge the reaction product at 3000 rpm for 10 min, repeating 5 times until the pH reaches 6. Further add the product to sufficient ethanol, sonicate in an ice bath for 2 h, and finally centrifuge at 4000 rpm for 20 min to form a layered Ti3C2T. x Nanosheet colloidal solution, take the upper layer of Ti3C2T x The material was added to 1 mL of (3-aminopropyl)trimethoxysilane (APS) solution and stirred at room temperature for 48 h. After centrifugation and washing, the product was dispersed in sufficient ethanol and then sonicated for 1 h under an inert atmosphere and ice bath to obtain APS-Ti3C2T. x MXene nanocolloid suspension;
[0044] S2. Take a certain amount of the APS-Ti3C2T x The MXene nanocolloid suspension was added to the tin oxide dispersion and mixed thoroughly to obtain the precursor.
[0045] The precursor obtained above was spin-coated onto a substrate (ITO) and annealed to obtain an electron transport layer; the annealing temperature was 150°C and the annealing time was 30 min.
[0046] The perovskite solution was then spin-coated onto the electron transport layer and annealed to obtain the perovskite layer; the annealing temperature was 150°C and the annealing time was 30 min.
[0047] The carbon paste was then coated onto the perovskite layer and annealed at 150°C for 30 minutes to obtain APS-Ti3C2T. x MXene's perovskite solar cells.
[0048] Example 2: A product containing DAMO-Ti3C2T x Fabrication of MXene perovskite solar cells
[0049] A type containing DAMO-Ti3C2T x MXene's perovskite solar cell has the following device structure: ITO (100nm) / Electron Transport Layer (ETL) (20nm) / Perovskite Layer (PVSK) (280nm) / Carbon Electrode (30μm).
[0050] The above contains DAMO-Ti3C2T x The fabrication method of MXene perovskite solar cells is as follows:
[0051] The preparation methods for ITO, perovskite layer, and carbon electrode are all processes and parameters well known to those skilled in the art.
[0052] Fabrication of the electron transport layer:
[0053] S1. Add 0.5 g LiF to 10 ml HCl (9 M) and stir for 5 min. Then, slowly add 0.5 g Ti3AlC2 over 5 min to avoid vigorous reaction. Stir the mixture continuously at 35 °C for 24 h. Centrifuge the reaction product at 3000 rpm for 10 min, repeating 5 times until the pH reaches 6. Further add the product to sufficient ethanol, sonicate in an ice bath for 2 h, and finally centrifuge at 4000 rpm for 20 min to form a layered Ti3C2T. x Nanosheet colloidal solution, take the upper layer of Ti3C2T x The material was added to 1 mL of N-[3-(trimethoxysilyl)propyl]ethylenediamine (DAMO) solution and stirred at room temperature for 48 h. After centrifugation and washing, the product was dispersed in sufficient ethanol and then sonicated for 1 h under an inert atmosphere and ice bath to obtain DAMO-Ti3C2T. x MXene nanocolloid suspension;
[0054] S2. Take a certain amount of the DAMO-Ti3C2T x The MXene nanocolloid suspension was added to the tin oxide dispersion and mixed thoroughly to obtain the precursor.
[0055] The precursor obtained above was spin-coated onto a substrate (ITO) and annealed to obtain an electron transport layer; the annealing temperature was 150°C and the annealing time was 30 min.
[0056] The perovskite solution was then spin-coated onto the electron transport layer and annealed to obtain the perovskite layer; the annealing temperature was 150°C and the annealing time was 30 min.
[0057] The carbon paste was then coated onto the perovskite layer and annealed at 150°C for 30 minutes to obtain DAMO-Ti3C2T. x MXene's perovskite solar cells.
[0058] Example 3: A type of product containing APTES-Ti3C2T x Fabrication of MXene perovskite solar cells
[0059] A type containing APTES-Ti3C2T x MXene's perovskite solar cell has the following device structure: ITO (100nm) / Electron Transport Layer (ETL) (20nm) / Perovskite Layer (PVSK) (280nm) / Carbon Electrode (30μm).
[0060] The above contains APTES-Ti3C2T x The fabrication method of MXene perovskite solar cells is as follows:
[0061] The preparation methods for ITO, perovskite layer, and carbon electrode are all processes and parameters well known to those skilled in the art.
[0062] Fabrication of the electron transport layer:
[0063] S1. Add 0.5 g LiF to 10 ml HCl (9 M) and stir for 5 min. Then, slowly add 0.5 g Ti3AlC2 over 5 min to avoid vigorous reaction. Stir the mixture continuously at 35 °C for 24 h. Centrifuge the reaction product at 3000 rpm for 10 min, repeating 5 times until the pH reaches 6. Further add the product to sufficient ethanol, sonicate in an ice bath for 2 h, and finally centrifuge at 4000 rpm for 20 min to form a layered Ti3C2T. x Nanosheet colloidal solution, take the upper layer of Ti3C2T x The material was added to 1 mL of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane solution and stirred at room temperature for 48 h. After centrifugation and washing, the product was dispersed in sufficient ethanol and then sonicated for 1 h under an inert atmosphere and ice bath to obtain APTES-Ti3C2T. xMXene nanocolloid suspension;
[0064] S2. Take a certain amount of the APTES-Ti3C2T x The MXene nanocolloid suspension was added to the tin oxide dispersion and mixed thoroughly to obtain the precursor.
[0065] The precursor obtained above was spin-coated onto a substrate (ITO) and annealed to obtain an electron transport layer; the annealing temperature was 150°C and the annealing time was 30 min.
[0066] The perovskite solution was then spin-coated onto the electron transport layer and annealed to obtain the perovskite layer; the annealing temperature was 150°C and the annealing time was 30 min.
[0067] The carbon paste was then coated onto the perovskite layer and annealed at 150°C for 30 minutes to obtain APTES-Ti3C2T. x MXene's perovskite solar cells.
[0068] Comparative Example 1:
[0069] The materials and preparation method used in Comparative Example 1 were the same as those in Example 1, the only difference being that Comparative Example 1 did not contain silane-functionalized Ti3C2T. x MXene.
[0070] Comparative Example 2:
[0071] The materials and preparation method used in Comparative Example 2 were the same as those in Example 1, the only difference being that Ti3C2T in Comparative Example 2 was different. x MXene was not functionalized with silane.
[0072] Test case
[0073] Figure 2 The APS-Ti3C2T in Embodiment 1 of the present invention is shown. x MXene and Ti3C2T without silane functionalization in Comparative Example 2 x The infrared spectrum of MXene, compared with that of unfunctionalized Ti3C2T x Compared to MXene, the APS-Ti3C2T x The presence of additional vibrational peaks for CH3, NH, and Si-O in MXene suggests that this may be due to Ti3C2T x The Ti-O-Si interaction between the MXene surface and APS enabled the successful attachment of APS to Ti3C2T. x The surface of MXene.
[0074] Figure 3 The APS-Ti3C2T in Embodiment 1 of the present invention is shown. x MXene and Ti3C2T without silane functionalization in Comparative Example 2 x X-ray photoelectron spectra of MXene, with the Si 2p spectrum shown. APS-Ti3C2T x MXene showed an additional Si 2p peak from APS, with the Si 2p peak around 102 eV corresponding to Si atoms in the adsorbed APS, further confirming that APS is attached to Ti3C2T. x surface.
[0075] Under standard test conditions (AM1.5, 25℃, 100W / m) 2 The performance data of the perovskite solar cells prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the short-circuit current density (J) was measured. sc ), open circuit voltage (V) oc The specific battery performance parameters, including conversion efficiency (PCE) and fill factor (FF), are shown in Table 1.
[0076] Table 1 Performance data of perovskite solar cells in the examples and comparative examples.
[0077]
[0078]
[0079] As can be seen from Table 1, the perovskite solar cell of the present invention has higher efficiency compared with the comparative perovskite solar cell.
[0080] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0081] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A perovskite solar cell containing silane-functionalized MXene, characterized in that, Includes an electron transport layer, which is made of silane-functionalized MXene-doped tin oxide; The silane has the general formula RSiY. m ,in, R is selected from an alkyl chain or alkoxy chain containing a polar group, wherein the polar group is selected from one or more combinations of halogen, amino, mercapto, epoxy, cyano, and quaternary ammonium groups. Y is selected from a hydrolyzable group, wherein the hydrolyzable group is selected from one or more combinations of halogen, methoxy, ethoxy or other alkoxy groups; m is the number of the hydrolyzable groups, and m = 1-3; The general formula for MXene is M n+1 X n T x ,in, M is selected from transition metal elements; the transition metal elements are selected from one or more combinations of Ti, Sc, Y, Zr, Hf, V, Nb, Ta, Cr, Mo, and W; X is C or N; n=1-4; T is selected from terminal functional groups; the terminal functional groups are selected from one or more combinations of -OH, =O, =S, =Se, =Te, -Br, -Cl or -F; x is the number of terminal functional groups, and 0 <x≤2。 2. The perovskite solar cell containing silane-functionalized MXene according to claim 1, characterized in that, The perovskite solar cell containing silane-functionalized MXene has a structure that, from bottom to top, includes a transparent conductive glass, an electron transport layer, a perovskite layer, and a carbon electrode.
3. The perovskite solar cell containing silane-functionalized MXene according to any one of claims 1-2, characterized in that, The method for preparing the electron transport layer includes the following steps: S1. Preparation of silane-functionalized MXene: The precursor MAX phase powder was placed in a lithium fluoride solution mixed with hydrochloric acid, stirred and reacted, and after centrifugation, the resulting product was added to ethanol, sonicated in an ice bath and centrifuged to obtain a layered MXene material; the layered MXene material was dispersed in a silane solution and stirred, washed, and the product was dispersed in a solvent and then sonicated in an inert atmosphere and ice bath to obtain a silane-functionalized MXene nanocolloid suspension. S2, Fabrication of the electron transport layer: The silane-functionalized MXene nanocolloid suspension was added to a tin oxide dispersion and mixed to obtain a precursor. The precursor was then spin-coated onto a substrate and annealed to obtain an electron transport layer.
4. The perovskite solar cell containing silane-functionalized MXene according to claim 3, characterized in that, The mass of the silane-functionalized MXene nanocolloid in S2 is 0.1%-30% of the mass of the tin oxide.
5. The perovskite solar cell containing silane-functionalized MXene according to claim 3, characterized in that, The annealing temperature in S2 is 100-180 ℃, and the annealing time is 20-40 min.
6. The perovskite solar cell containing silane-functionalized MXene according to claim 3, characterized in that, The spin coating speed is 3000-5000 rpm / s, and the spin coating acceleration is 1000-2000 rpm / s.
7. The perovskite solar cell containing silane-functionalized MXene according to claim 3, characterized in that, The solvent is selected from one or more of deionized water, acetonitrile, N,N-dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, methanol, ethanol, isopropanol, n-butanol, tetrahydrofuran, chloroform, diethyl ether, isopropyl ether, n-butyl ether, trichloroethylene, diphenyl ether, dichloromethane, dichloroethane, toluene, xylene, chlorobenzene, dichlorobenzene, trichlorobenzene, cyclohexane, and hexane.
Citation Information
Patent Citations
Perovskite solar cell and preparation method thereof
CN111564560A